PHYTOCHEMICAL ANALYSIS, ANTIMICROBIAL AND ANTITUMOUR SCREENING OF ENDOPHYTES OF TINOSPORA CORDIFOLIA - SAVITHA DESAI; RITA METRANI; SONAM VANTAMURI; VARUNI GINIGERI; KIRTI PHADKE; BASAVARAJ HUNGUND (International Journal of Pharma and Bio Sciences, 2012)
Tinospora cordifolia, commonly known as ‘Guduchi’ in India is a medicinal plant which is used to treat various diseases. Phytochemical analysis of plant revealed the presence of alkaloids, flavonoids, steroids, saponins, total phenols, cardiac glycosides and reducing sugars. The total phenol content was 0.39 mg GEA/mg, 0.25 mg GEA /mg for leaf and stem respectively. These findings could be useful for both pharmaceutical companies and research institutes in the development of new drugs. Out of nine endophytic fungal isolates, eight belonged to Penicillium sp. and one remained unidentified. Fungal extracts were tested for antimicrobial and antitumor activity. Result showed that endophytes had good antibacterial activity compared to antifungal activity. Antitumor activity assayed by SRB assay method using MCF and SiHA cell lines was negative for endophytes selected. Since endophytes are potent source of the secondary metabolites and also have antibacterial property they can be used for pharmaceutical applications.